ANALISIS MASHLAHAT MURSALAH KEIKUTSERTAAN INDONESIA DALAM ASEAN ECONOMIC COMMUNITY - Fahlul Amri; Hendri Tanjung; Fahruddin Sukarno (Univ Ibn Khaldun Bogor, 2019)
Methodology uses a qualitative method. The characteristic on it is direction to describe a case with understanding of meaning and its problems, so that data analyzing which used is analytic descriptive. Collecting data uses observation method, interview, documentaries and ends to conclusion. The result of this research and its analyzing about Mashlahat Mursalah in AEC 2015 to Indonesia shows that many domain advantages and positives side. Indonesia would become a wealth region and competitive with good economic progressing and reducing poverty and it deviation social and economic. But, to reach it is not easy at all and need a hard and serious work to face it. Indonesia has big potential such as population, natural resources, wide geography and biggest PDB in ASEAN so that Indonesia become main player in ASEAN Economic Community 2015.